2021
DOI: 10.18502/ssu.v29i3.6203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medication Errors from the Perspective of Nurses in the ICUs of Yazd City

Abstract: Introduction: Medication error is one of the most common errors in the medical context which has a great importance in the ICUs due to the patients’ inability and vulnerability in participating in the medication therapy. The aim of this study was to determine frequency, types, and reasons of medication errors in the ICUs. Methods: This was a cross-sectional descriptive study, which was conducted on 105 nurses working in the ICUs located in hospitals of Yazd City in 2017 on the basis of census sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Furthermore, there was a signi cant statistical relationship between work experience, participation in medication error workshops, and perception of medication errors, which is consistent with the studies byKhalid Al-Mugheed et al (2023) and Wondmieneh et al (2019), but not with the study by Kermanshahi et al (2016)(42)(43)(44). This difference may be due to the type of department and other relevant factors, as their research was speci cally conducted on pediatric nurses.In addition, in this study, a signi cant statistical relationship was found between marital status and perception of medication errors, which is consistent with the study by Saedi et al (2020), but not with the study by Aghili Dehkhordi et al (2019) (45, 46).Stepwise multiple linear regression analysis showed that "patient-centered medication management" was a stronger predictor of medication safety competency and perception of medication errors compared to other variables, which is consistent with the studies by Bijani et al (2024) and Salmani et al (2018)(33,47).Furthermore, in this study, there was a direct and signi cant relationship between the scope of risk management and perception of medication errors, which is consistent with the study by Dehghan Nayeri et al (2021). Nayeri's research also con rms the results of the present study, showing a signi cant reduction in medication errors among nurses in the test group with proper risk management (48).…”
supporting
confidence: 85%
“…Furthermore, there was a signi cant statistical relationship between work experience, participation in medication error workshops, and perception of medication errors, which is consistent with the studies byKhalid Al-Mugheed et al (2023) and Wondmieneh et al (2019), but not with the study by Kermanshahi et al (2016)(42)(43)(44). This difference may be due to the type of department and other relevant factors, as their research was speci cally conducted on pediatric nurses.In addition, in this study, a signi cant statistical relationship was found between marital status and perception of medication errors, which is consistent with the study by Saedi et al (2020), but not with the study by Aghili Dehkhordi et al (2019) (45, 46).Stepwise multiple linear regression analysis showed that "patient-centered medication management" was a stronger predictor of medication safety competency and perception of medication errors compared to other variables, which is consistent with the studies by Bijani et al (2024) and Salmani et al (2018)(33,47).Furthermore, in this study, there was a direct and signi cant relationship between the scope of risk management and perception of medication errors, which is consistent with the study by Dehghan Nayeri et al (2021). Nayeri's research also con rms the results of the present study, showing a signi cant reduction in medication errors among nurses in the test group with proper risk management (48).…”
supporting
confidence: 85%
“…A high rate of medication error was reported in our study. In a study in Yazd City (the center of Iran), Bagheri et al reported that 66.7% of nurses experienced medication errors, and 40.6% performed medication errors only once (19). In the study by Dashti et In the present study, most medication errors were reported in emergency wards.…”
Section: Discussionsupporting
confidence: 44%
“…A high rate of medication error was reported in our study. In a study in Yazd City (the center of Iran), Bagheri et al reported that 66.7% of nurses experienced medication errors, and 40.6% performed medication errors only once ( 19 ). In the study by Dashti et al in the city of Ardabil in northwestern Iran, the incidence rate of at least one medication error in the nurses under study during the past 6 months was 86.4%, with an average of 3.6 errors per nurse ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the results of a study conducted by Mohatashami, et al (2015), it was found that hardiness and resilience have a positive and significant relationship (p<0.001 and β=0.34). Then, the results of a study by Bafroe et al (2015) showed significantly correlated hardiness and resilience in Type 2 diabetes patients. On the other hand, research conducted by Setyanugraha (2019) found that there was no significant positive relationship between the hardiness and resilience of cyberbullying victims (r = 0.045 p = 0.689).…”
Section: Introductionmentioning
confidence: 98%